Experience of Treating Critically Ill COVID-19 Patients in Daegu, South Korea - Kyeong-Cheol Shin (Tuberculosis and Respiratory Diseases, 2021)
At the beginning of February 2020, Daegu faced a serious situation due to the rapid outbreak of coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus-2. The healthcare system in Daegu Metropolitan City was ill-prepared for this sudden disaster situation. The COVID-19 pandemic is still ongoing in South Korea. Daegu has limited medical resources compared to the Seoul Metropolitan Area, and it is hypothesized that a review of the outbreak therein could provide information that will be valuable for dealing with future outbreaks. The likelihood of death due to COVID-19 depends on the capacity of the area for the treatment of critically ill patients. This report reviews the overall treatment process followed for critically ill patients in Daegu.